Bacterial Contamination of Toothbrushes and their Disinfection by 4% Edta, 10% Sodium Perborate and 3% Neem Juice: A Clinico -Microbiology Study - Sheikh, Nilofer Sultan; Rajhans, Neelima S.; Moolya, Nikesh; Mhaske, Nilkanth; Frenandes, Gabrieala Jude; Sudeep, H.M. (The Journal of Dentists, 2014)
Aim: The aim of this randomized clinical trial was to evaluate the bacterial survival rate on toothbrushes and efficacy of their decontamination by 4% disodium ethyl diamine tetra acetic acid [EDTA], 10% sodium perborate and 3% neem juice. Methods: Forty subjects with chronic periodontitis enrolled to this randomized controlled clinical trial were provided with autoclaved toothbrushes which were free from microorganisms. Brushing instructions were given to each participant. Toothbrushes were collected from all study participants after one week and were placed with head down position in autoclaved test tube containing sterile peptone water. Toothbrushes collected were sent for aerobic culture in laboratory for growth of micro-organisms. Incubation was done for 24 hours at 37˚C.The toothbrushes were then divided into four groups and immersed in disinfectants like 4% disodium EDTA, 10% sodium perborate and 3% neem juice. Their efficacy was evaluated by aerobic culture analysis and chi – square test was used for statistical analysis of the data. Results: The results obtained showed that 4% disodium EDTA and 3% neem juice showed 100% efficacy, whereas 10% Sodium perborate showed 40% effectiveness in decontaminating the toothbrushes. Distilled water as a control showed least effectiveness in cleaning toothbrushes. Conclusion: The present data appeared to indicate that 4% Disodium EDTA and 3 % Neem juice are equally effective but 3% Neem juice may be considered non-toxic, cost effective and quite feasible for disinfection of toothbrushes.